The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/15623599.2020.1832182
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to green building project financing: an empirical study in Ghana

Abstract: This study examines the perception of professionals in the Ghanaian construction industry regarding the obstacles to green building project financing. Following an extensive critical comparative review of literature resulting in the identification of ten potential obstacles, a cross-sectional survey was conducted among 520 construction industry professionals. Data obtained from the survey were analysed using both descriptive and inferential statistics. The findings from the study revealed that split incentives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…In the view of Darko et al (2017a, b), this factor is a critical driver for implementing green building technologies worldwide. Agyekum et al (2020a, b) also identified this factor as an essential driver of green building certifications in Ghana. In confirmation of that postulated by Ross (2015), the Ernest and Young (EY) group indicated that one of the significant drivers of issuance of green bonds by companies is to enhance their brand as an environmentally conscious organisation (EY, 2015).…”
Section: Literature Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…In the view of Darko et al (2017a, b), this factor is a critical driver for implementing green building technologies worldwide. Agyekum et al (2020a, b) also identified this factor as an essential driver of green building certifications in Ghana. In confirmation of that postulated by Ross (2015), the Ernest and Young (EY) group indicated that one of the significant drivers of issuance of green bonds by companies is to enhance their brand as an environmentally conscious organisation (EY, 2015).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Though these opportunities in the various sectors were well reported by Partnership for Action on Green Economy, PAGE (2015), little was said regarding green financing opportunities for the building construction sector. A study conducted by Agyekum et al (2020a, b) reveals that the building construction sector encounters some obstacles when it comes to green building project financing. The key blocks were identified to include split incentives, risk-related barriers, capital expenditure, lack of incentives and initial capital cost.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other sectors, the construction industry is noted for its contribution to the greenhouse gas emissions [71]. This notwithstanding, there have been numerous efforts put in place by various sectors to control such emissions.…”
Section: Sustainable Cities and Communities (Sdg 11)mentioning
confidence: 99%